The adaptive potential of Populus balsamifera L. to phenology requirements in a warmer global climate. Issue 5 (24th October 2012) - Olson, Matthew S.; Levsen, Nicholas; Soolanayakanahally, Raju Y.; Guy, Robert D.; Schroeder, William R.; Keller, Stephen R.; Tiffin, Peter
Abstract The manner in which organisms adapt to climate change informs a broader understanding of the evolution of biodiversity as well as conservation and mitigation plans. We apply common garden and association mapping approaches to quantify genetic variance and identify loci affecting bud flush and bud set, traits that define a tree's season for height growth, in the boreal forest tree Populus balsamifera L. (balsam poplar). Using data from 478 genotypes grown in each of two common gardens, one near the southern edge and another near the northern edge of P. balsamifera's range, we found that broad‐sense heritability for bud flush and bud set was generally high (H2 > 0.5 in most cases), suggesting that abundant genetic variation exists for phenological response to changes in the length of the growing season. To identify the molecular genetic basis of this variation, we genotyped trees for 346 candidate single nucleotide polymorphisms (SNPs) from 27 candidate genes for the CO/FT pathway in poplar. Mixed‐model analyses of variance identified SNPs in 10 genes to be associated with variation in either bud flush or bud set. Multiple SNPs within FRIGIDA were associated with bud flush, whereas multiple SNPs in LEAFY and GIGANTEA 5 were associated with bud set. Although there was strong population structure in stem phenology, the geographic distribution of multilocus association SNP genotypes was widespread except at the most northern populations, indicating that geographic regions may harbour sufficient diversity in functional genes to facilitate adaption to future climatic conditions in many sites.